Competence for Sustainability: Prevention of Dis-Balance in Higher Education: The Case of Cooperation While Educating Future Law Enforcement Officers - Vaiva Zuzeviciute; Birute Praneviciene; Zaneta Simanaviciene; Violeta Vasiliauskiene (Montenegrin Journal of Economics)
In the twenty-first century, social, environmental and technological challenges demand new knowledge and educational innovations. University has become an organization which has an objective to operate more efficiently in relation to transformations to sustainability. Businesses (in a wider sense: employers) and universities should take specific steps in order to intensify the cooperation in producing sustainability informed professional who will be able to engage with the economic and social dimensions of sustainability. The purpose of this paper is to conceptualize competence for sustainability as the prevention of disbalance in higher education. The case of cooperation while educating future law enforcement officers is at the focus of analysis. The methodology of this study relies on two baselines. Our first baseline for further analysis is the statement that sustainability informed professionals may only be educated if a sustainable education in higher education is an overarching reality. Firstly, the concept of sustainability is explored using descriptive methodology. Secondly, the forms of manifestation of sustainability will be presented through the lens of examples: the case study of Lithuania, illustrated by experiences of two Lithuanian universities. The conclusions reached are as following: only the balanced education of all the enumerated (and may be even more) sub competencies may lead to a sustainability – informed professional. It is important not to emphasize instrumental sub competence at the expense of personal or social development of a student/future professional.